Comparison of tyrosine kinase inhibitors in the treatment of metastatic renal cell carcinoma with rhabdoid and sarcomatoid differentiations - Kun Wang; Pengqiang Duan; Xusheng Chen; Qing Yang; Guowei Feng; Lei Diao; Zhenting Zhang; Xin Yao (Cancer Medicine, 2023)
Abstract Objective To investigate the efficacy of tyrosine kinase inhibitors (TKIs) in the treatment of metastatic renal cell carcinoma (mRCC) with rhabdoid (mRCC‐R) and sarcomatoid (mRCC‐S) differentiations. Materials and Methods In this single‐institutional cohort study, we included patients with RCC with rhabdoid (RCC‐R) and sarcomatoid (RCC‐S) differentiation, who were treated with TKIs after metastasis at our institute from 2013 to 2021. Patient characteristics, treatments, and clinical outcomes were recorded and analyzed. Results We identified 111 patients with RCC‐R or RCC‐S differentiations, of which 23 patients were included in the final analysis. Of the 23 patients, 10 (43.5%) were grouped as mRCC‐R and 13 (56.5%) as mRCC‐S. At a median follow‐up of 40 months, mRCC‐R and mRCC‐S progressed in 7 of 10 and 12 of 13 patients, respectively. In addition, four and eight patients died in the mRCC‐R and mRCC‐S groups, respectively. The median progression‐free survival (PFS) of the two groups was 19 months (mRCC‐R: 95% confidence interval [CI] 4.08–33.92) and 7 months (mRCC‐S: 95% CI 2.03–11.96), while the median overall survival (OS) was 32 months and 21 months, respectively. mRCC‐S had a worse prognosis than mRCC‐R. Based on the univariate Cox regression model, single metastasis or multiple metastasis of tumor, rhabdoid differentiation, and sarcomatoid differentiation were predictors of PFS but not OS. Conclusion The efficacy of TKIs in the treatment of mRCC‐R and mRCC‐S may be different.